KONSEP PENDIDIKAN ISLAM TENTANG TANGGUNG JAWAB ORANG TUA TERHADAP AKHLAK ANAK - Rahmani N (Yayasan Pondok Pesantren Rasyidiyah Khalidiyah Amuntai, 2025)
This research examines the parental responsibility in educating children from the perspective of Islamic teachings. The study highlights that children are born in a pure state, and parents play the primary role in shaping their faith, character, and behavior. Islamic education emphasizes early religious nurturing through teaching the Qur’an, instilling love for the Prophet, guiding children to distinguish between halal and haram, and habituating them in acts of worship. The article also discusses how parents must protect children from immoral traits such as envy, arrogance, greed, and backbiting. The research is descriptive-qualitative, relying on Islamic texts, scholarly opinions, and classical references. The findings reveal that the family is the child’s first and most influential educational environment, and strong parental guidance forms righteous and morally upright individuals.